2014
DOI: 10.1155/2014/208597
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Von Willebrand’s Syndrome in Systemic Lupus Erythematosus

Abstract: Acquired von Willebrand syndrome (AVWS) is an uncommon, underdiagnosed, and heterogeneous disease which is increasingly recognized as a cause of bleeding diatheses. Systemic lupus erythematosus (SLE) is an infrequent cause of AVWS. Herein, we report a case of AVWS diagnosed during the initial presentation of SLE in a previously healthy young man with no family history of bleeding diathesis who presented with worsening epistaxis, gastrointestinal bleeding, and anasarca. He was found to have severe anemia and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…2 The first case of AVWS secondary to systemic lupus erythematosus (SLE) was reported by Simone et al 3 in 1968. Although this association is infrequently described in literature, 1,3,4 even less frequent is its presentation with clinical and laboratory features resembling a severe VWD phenotype. 5 Most cases have mild to moderate bleeding tendency, with laboratory characteristics similar to inherited VWD type 1.…”
Section: Dear Editormentioning
confidence: 88%
See 1 more Smart Citation
“…2 The first case of AVWS secondary to systemic lupus erythematosus (SLE) was reported by Simone et al 3 in 1968. Although this association is infrequently described in literature, 1,3,4 even less frequent is its presentation with clinical and laboratory features resembling a severe VWD phenotype. 5 Most cases have mild to moderate bleeding tendency, with laboratory characteristics similar to inherited VWD type 1.…”
Section: Dear Editormentioning
confidence: 88%
“…Until the 1989 discovery of HCV, 3 almost all haemophilia patients treated with clotting factor products were infected with HCV. 4 The clinical presentation of HCV is characterized by chronic liver disease that can progress to fibrosis with development of (de)compensated cirrhosis and hepatocellular carcinoma. Haemophilia A murine models that mimic patients with severe haemophilia A are currently available.…”
Section: Does Haemophilia Slow Down the Development Of Liver Fibrosis?mentioning
confidence: 99%
“…For AVWS and SLE, steroids and cyclophosphamide are effective in controlling hemorrhage (25-28). Recent studies have reported that rituximab is used to treat AVWS in adolescent SLE (29)(30)(31), and bleeding in both patients has been effectively controlled. In this case, the activity of VWF and FVIII returned to normal levels after methylprednisolone pulse therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, although SMZL was quite advanced, the patient refused to receive conventional chemotherapy and instead chose rituximab monotherapy. In the literature, rituximab has not been effective in AVWS associated with MGUS (15-17) or with lymphoplasmacytic lymphoma (18), although it has been effective in AVWS associated with B cell lymphoma (MALT lymphoma) (10,11), monoclonal B cell lymphocytosis (19), essential mixed cryoglobulinemia (20), and SLE (21,22). Although the lymphadenopathy in our case showed mild shrinkage, the AVWS was not resolved.…”
Section: Discussionmentioning
confidence: 99%